Reply to comment on Ben Dor Y. et al. "Varves of the Dead Sea sedimentary record." Quaternary Science Reviews 215 (2019): 173–184. (1st March 2020) - Ben Dor, Yoav; Neugebauer, Ina; Enzel, Yehouda; Schwab, Markus J.; Tjallingii, Rik; Erel, Yigal; Brauer, Achim
Abstract: In the comment on "Varves of the Dead Sea sedimentary record." Quaternary Science Reviews 215 (Ben Dor et al., 2019): 173–184. by R. Bookman, two recently published papers are suggested to prove that the interpretation of the laminated sedimentary sequence of the Dead Sea, deposited mostly during MIS2 and Holocene pluvials, as annual deposits (i.e., varves) is wrong. In the following response, we delineate several lines of evidence which coalesce to demonstrate that based on the vast majority of evidence, including some of the evidence provided in the comment itself, the interpretation of these sediments as varves is the more likely scientific conclusion. We further discuss the evidence brought up in the comment and its irrelevance and lack of robustness for addressing the question under discussion. Highlights: The interpretation of laminations in the sedimentary record of the Dead Sea is discussed. There is robust evidence for interpreting laminated sedimentary sequences of the Dead Sea as varves. The recent claims made to question annual aragonite deposition in the Dead Sea are shown to be premature and irrelevant.